Timing-dependent effects of melatonin supplementation on exercise performance and exercise-induced muscle damage: a systematic review and meta-analysis - Guo, J.; Zhou, L.; Gu, J.; Sun, J.; Liu, G.; Wei, C. (Frontiers in Nutrition, 2026)
Background: Melatonin, an endogenous neurohormone with both chronobiotic and antioxidant properties, has been proposed as a nutritional aid for recovery and performance optimization. However, its timing-dependent effects on athletic performance remain unclear. This systematic review and meta-analysis aimed to evaluate the timing-dependent effects of melatonin supplementation on exercise performance and exercise-induced muscle damage in athletes and physically active individuals.